Prevalence and relationship with health of off-label and contraindicated drug use in the United States: a cross-sectional study - Katharina E. Blankart; Frank R. Lichtenberg (Journal of Pharmaceutical Policy and Practice)
Background: Off-label and contraindicated prescription drug use can result in adverse health outcomes. Despite concerns, the extent and characteristics of such usage patterns remain underexplored in the American population. We conducted a cross-sectional study analysing outpatient prescription data between 2016 and 2021 to determine the prevalence of off-label and contraindicated drug use.Methods: The study used labelling information from DrugCentral and the Medical Expenditure Panel Survey, focusing on the American non-institutionalised population. We analysed 9872 drug-indication and 34,138 drug-contraindication pairs among 46,770 patients and 1,596,753 prescriptions. Linear and probit regressions, and a double machine learning approach, were employed to assess associations between off-label/contraindicated use, health status, and healthcare utilisation, adjusting for demographic and health-related factors.Results: Overall, 75% of prescriptions were for labelled indications, while 25% were off-label; 54% were contraindicated. Only 33% of prescriptions were both indicated and not contraindicated. Off-label prescriptions had a lower contraindication rate (48.8%) compared to indicated prescriptions (56.2%). Improved health status and reduced medical expenditure correlated with lower off-label prescription rates. Notably, newer drugs (post-1997) had a higher rate of prescriptions that were both indicated and not contraindicated (43%) compared to older drugs (pre-1979, 21%). Patterns of off-label and contraindicated use were consistent across racial and educational demographics.Conclusion: Off-label and contraindicated drug use is prevalent in outpatient prescriptions and is associated with worse health outcomes and increased healthcare utilisation. These findings suggest a need for enhanced monitoring and regulatory measures to minimise risks associated with inappropriate prescription practices.